Assessing Mandeh Region as the Center of Marine Ecotourism in West Sumatra Province, Indonesia: Mass Tourism Issue and Vulnerability Aspects - Ulung Jantama Wisha; Try Al Tanto; Nia Naelul Hasanah Ridwan; Guntur Adhi Rahmawan; Ruzana Dhiauddin; Koko Ondara; Wisnu Arya Gemilang (Jurnal Segara, 2021)
Nowadays, Mandeh Region has developed significantly as the center of marine ecotourism in West Sumatra Province. Many local and international tourists were visiting this site. Due to those conditions, many threats emerged, such as mass tourism evoking damages and pollutions. This study aimed to examine the feasibility of the Mandeh Region for tourism activity and identify the impacts of mass tourism. A direct survey has been conducted. We assessed water quality, accessibility, and social conflicts using a scoring method. A modified matrix categorizing some parameters as the underlying data for marine tourism sustainability was used. We also developed Smartline and CVI model to assess the vulnerability level along Mandeh coastal bay. Local zonation was recommended to reduce more environmental damages. We examined the feasibility of the Mandeh region as a place for ecotourism that reached 71.12 %, indicating this area is sufficiently feasible. The absence of local regulations before the Mandeh region was established as the center of marine ecotourism resulted in mass tourism phenomena that elevated marine litter accumulation. Moreover, the development of many resorts near the coast has recently played a role in triggering pollution and damage. Advanced regulation and management are necessary to diminish negative impacts on both the environment and society.